ANALYSIS OF OCCUPATIONAL SAFETY AND HEALTH (OSH) RISKS IN THE TRANSPORTATION PROCESS OF HAZARDOUS AND TOXIC WASTE (B3) USING THE HAZOP METHOD AND RISK MATRIX - Andrea Felic Lim; Kevin Jerrykent; Uni Pratama Pebrina Br Tarigan (RADJA PUBLIKA, 2026)
Occupational safety and health (OSH) is an important aspect of industrial activities, particularly in the transportation of hazardous and toxic waste (B3), which poses high potential risks to workers, the environment, and the surrounding community. PT.XYZ, as a hazardous waste transportation service company, faces various potential hazards at each stage of its operational process, including vehicle preparation, loading, transportation to the destination, unloading, as well as administration and housekeeping activities. This study aims to identify potential hazards, analyze the level of occupational safety and health risks, and formulate risk control recommendations in the hazardous waste transportation process at PT.XYZ. The research method used in this study is descriptive-analytical research with qualitative and quantitative approaches. Hazard identification was carried out using the Hazard and Operability Study (HAZOP) method based on field observations, interviews, and documentation studies. Risk level assessment was conducted using the Risk Matrix method by applying likelihood and severity parameters to classify risks into low, medium, high, and extreme categories. The results show that there are 20 potential hazards identified across all stages of the hazardous waste transportation process. The risk level recapitulation indicates that high and medium risk categories each account for 45%, extreme risk accounts for 10%, and no risks fall into the low category. Extreme risks were found during the transportation stage to the destination, particularly those related to driver fatigue and uncontrolled vehicle speed. Based on these findings, risk control recommendations were formulated using a risk control hierarchy approach, including administrative controls, engineering controls, and the use of personal protective equipment. The implementation of these recommendations is expected to reduce OSH risk levels and improve occupational safety and health performance in the hazardous waste transportation process at PT.XYZ.